Beyond the antibody: B cells as a target for bacterial infection. Issue 5 (18th January 2019) - García‐Gil, Abraham; Lopez‐Bailon, Luis Uriel; Ortiz‐Navarrete, Vianney
Abstract: It is well established that B cells play an important role during infections beyond antibody production. B cells produce cytokines and are APCs for T cells. Recently, it has become clear that several pathogenic bacterial genera, such as Salmonella, Brucella, Mycobacterium, Listeria, Francisella, Moraxella, and Helicobacter, have evolved mechanisms such as micropinocytosis induction, inflammasome down‐regulation, inhibitory molecule expression, apoptosis induction, and anti‐inflammatory cytokine secretion to manipulate B cell functions influencing immune responses. In this review, we summarize our current understanding of B cells as targets of bacterial infection and the mechanisms by which B cells become a niche for bacterial survival and replication away from extracellular immune responses such as complement and antibodies. Abstract : Review on how B cells are infected by different bacteria and the implications this has for B cell function and bacteria survival.